Social, Emotional and Behavioral Screening Profiles Among Students in a Large Urban School District. (July 2023) - Robinson-Link, Patrick; Fowler, Danielle; Daniels, Brian; Battal, Jill
Social, emotional, and behavioral (SEB) screening frequently employs a variable-based approach wherein individual scale scores indicate risk. However, a person-centered approach wherein risk is indicated by profiles, or constellations of scores across all scales, could help schools prioritize students based on the pervasiveness of SEB needs and match students to appropriate interventions. This study used latent profile analysis (LPA) to identify profiles within two diverse student samples ( n = 16, 270 in year one; n = 4019 in year two) based on teacher ratings on the Behavior Intervention Monitoring Assessment System, Second Edition (BIMAS-2). Results suggested four profiles including one profile with elevated risk across all scales, one profile with low behavioral risk and above average social functioning, one profile with borderline risk across all scales, and one profile with typical scores across most scales. Implications for linking universal screening to intervention are discussed. Impact and Implications: Many school districts employ universal screening to prevent and address wide-ranging student needs. Grouping students based on shared sets of needs has the potential to efficiently identify and prioritize students with pervasive risk in order to match them to comprehensive services. Results from this study capture the first attempt to identify student need profiles using BIMAS-2 scores. Future research should refine this process to derive more usable and consistent student profiles allowing direct links to comprehensive student services.